The Impact Of Consumer Trust On Purchase Interest In Shopee (Study Of Economics Education Students at FKIP USK) - Zafirah Zafirah; Amrusi Amrusi; Achmad Mustofa* (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This study aims to determine the effect of consumer trust on purchase intention on the online shopping site Shopee. This research uses a quantitative approach with descriptive methods. The population in this study were Economics Education students at the Faculty of Teacher Training and Education at the Syiah Kuala University (FKIP USK). The sample used was 47 respondents with the accidental sampling method. Meanwhile, data collection techniques used library research and field research. The data analysis technique used is simple linear regression analysis and t test. Based on the results of the regression test, Y = 4.576 + 0.435X. Then the t test at a significant level of 5%, the hypothesis is accepted, as evidenced by the value of t_count = 6.375 t_table = 2.0141. The coefficient of determination (R Square) of 0.475 or equal to 47.5% means that the consumer trust variable affects the purchase intention variable, while the remaining 52.5% is influenced by other variables. The conclusions from this study indicate that consumer trust has a positive and significant effect on purchase intention on the online shopping site Shopee among students.